Comparison Study of the Cross – Organizational Cultural Between Public University Institution and State-Owned Company in Indonesia - Rinda Oktia Cahyaningsih; Adithya Sudiarno (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2022)
One of the proponents of economics power is the success of business, the achievement of targets in workplace. The presence of generation millennials in majority and the increasingly rapid use of technology in Industrial Era 4.0 will have an impact on organizational culture in the workplace. This study aims to examine the cross organizational cultural in both institutions Public University and State-Owned Company to analyze the organizational culture modelling its significant influence on organizational performance. The analysis results of cross organizational culture modelling to provide recommendation for the application of organizational culture in both institutions consist of behavior, leadership value, etc. The conceptual modeling that used in this study consisted of six latent variables related to organizational culture and generation millennials with two mediating variables can significantly influence Organizational Performance. This model is then tested using the Structural Equation Modeling (SEM) method. The results show that on the object of Public University all variables have a significant effect, except for one insignificant variable: Transformational leadership on Organizational Citizenship Behavior. Meanwhile, State-Owned Company all variables have significant influence, except for 3 variables: Transformational leadership on Organizational Citizenship Behavior, as well as Transformational leadership and Organizational citizenship behavior on organizational performance.